The naturalization of women's ability to care and its discursive effects on maternal subjectivation (Research, Society and Development, 2022)
Objective: the objective was to investigate in the discourses of primiparous women the discursive effects of the naturalization of the ability to care as an essentially feminine attribute, in the processes of maternal subjectivation. Method: This was an exploratory field research, according to a qualitative approach. The sample consisted of 9 primiparous women residing in the city of João Pessoa and in the interior of Paraíba. The instruments used were: Semi-structured interview composed of guiding questions and structured according to the objective of the study and a sociodemographic questionnaire. The interviews were analyzed through discourse analysis and socio-demographic data were analyzed through descriptive statistics. Results: Based on the procedures mentioned above, we can assume that two large units of analysis emerged, designated as "Continuous mental load: a mother's head doesn't stop" and "Paternal disresponsibility in the care economy: "he is not very good", these are some of the discursive effects resulting from discursive practices that naturalize in women the ability to care, reverberating in the ways in which women experience themselves in the process of maternal subjectivation. Conclusions: It is concluded that the naturalization of care, while romanticizing parental care as a normative maternal practice, moralizes maternal practice as a moral action of women. The effects of this have addressed women to depotentiating motherhood experiences, mainly because it reinforces and/or causes a progressive denial of the existence of women as subjects of action, since this normalization is nourished from practices that dehumanize women.